Macroprudential Regulation and Sector-Specific Default Risk - Belkhir, Mohamed (IMF Working Papers; Working Paper, 2022)
This paper studies the transmission of macroprudential policies across both financial and non financial sectors of the economy. It first documents that tighter macroprudential regulations implemented in Europe over the period 2008-2017 lowered default risk not only in the financial, but also in non-financial sectors. Second, the paper analyzes the impact of two reforms in the macroprudential framework. Higher capital requirements improve the long-run resilience of the financial sector but at the cost of raising long-term default risk in non-financial sectors. Strengthening the resolution framework for failing banks has beneficial long-run effects on the default risks of the financial and non-financial sectors. Our results concur with the literature documenting how banks adjust their balance sheet composition and credit supply in reaction to changes in their regulatory environment.